Is Pacifism an Ideology? - Klein, Rebekka A. (Studies in Christian ethics, 2018)
This article takes up the current debate on populism and democracy and deals with the philosophical critique that the twentieth-century idea of pacifism represents an (apolitical) ideology, the misguided nature of which must be debunked. In this context, the term ideology is referred to with a post-Marxist understanding, which interprets ideology as a collective fantasy structuring our social reality by way of a practice of disguise. Hence, the question will be raised as to whether modern religions, such as neo-Buddhism or Christianity, are well advised to appropriate the idea of pacifism in order to renew their imaginary register of peace and non-violence. In conclusion, it will be argued that the imagination and promise of a peaceful community is among the biblical motives that are the source of Christian faith. However, in order to prevent a political force from turning into an ideology, biblical motives have to be interpreted from the perspective of a negative Christology, which sees pacifism as an impossible project and thus liberates us from the pitfalls of human desire.